Real-life challenge: training program on drug use and adolescence in primary health care - Bruna Antunes de Aguiar Ximenes Pereira; Renata Cruz Soares de Azevedo
ABSTRACT Guidelines emphasize the importance of approaching substance use by adolescents, particularly in primary health care. However, there are problems with its incorporation. The objective of this study was to present the training stages on the theme for professionals in primary health care. Researchers conducted logistic structuring, content elaboration and evaluation of difficulties before and after training. Sixty percent of professionals involved in the care of adolescents in a medium-sized city participated in the study. More than half of them stated having difficulties in the approach, mainly theoretical limitations and short consultations. After the training, the professionals informed whether they felt more prepared, but practical difficulties remained.